The Intersection of Islamic Religious Education and Character Formation in Indonesia: A Sociological Perspective on (SMK) Sekolah Menengah Kejuruan Jamiah Al-Aziziyah - Mukhtar, Masrizal; Abdullah, Amiruddin; Ependi, Muhammad (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study explores the role of Islamic Religious Education (PAI) in shaping the moral and ethical character of students at SMK Jamiah Al-Aziziyah from a sociological perspective. Using a qualitative approach, data were collected through interviews with PAI teachers and students, observations, and document analysis. The findings show that PAI significantly contributes to character formation by fostering values such as honesty, discipline, responsibility, and politeness. These values are instilled through formal lessons and internalized through social interactions at school, including peer communication, collaboration in religious activities, and role modeling by teachers. Despite these positive outcomes, challenges such as negative social media influences and limited parental engagement persist. The study highlights the need for a collaborative framework involving schools, families, and communities to address external challenges and sustain moral development. It also calls for future research to integrate family and community roles more effectively into character education initiatives